2014
DOI: 10.11604/pamj.2014.18.42.3651
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and platelet counts in type 2 Diabetes: Mellitus on treatment and non-diabetic mellitus controls in Lagos, Nigeria

Abstract: IntroductionThe Mean platelet volume and platelet counts are indicators of thrombotic potentials, and risk factors for microvascular complications in diabetics. This study aimed to establish variations in platelet counts and mean platelet volume in type 2 diabetic patients on treatment and non-diabetic controls.MethodsThis was an unmatched case-control study involving 200 participants consisting of 100 diabetics and 100 non-diabetic controls. Four and half milliliters of blood was collected from diabetics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
47
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 29 publications
15
47
7
Order By: Relevance
“…So the overall mean platelet count for ischemic stroke was much lower of the control values. It is however in contrast to the findings of a ischemic stroke there were a lot of studies revealed a higher mean platelet count for diabetics than for the controls (Akinsegun et al, 2014). But our results showed the decrease of platelet count in patients with stroke complicated by type 2 diabetes, although this decrease was less than in case of stroke alone.…”
Section: Discussioncontrasting
confidence: 99%
“…So the overall mean platelet count for ischemic stroke was much lower of the control values. It is however in contrast to the findings of a ischemic stroke there were a lot of studies revealed a higher mean platelet count for diabetics than for the controls (Akinsegun et al, 2014). But our results showed the decrease of platelet count in patients with stroke complicated by type 2 diabetes, although this decrease was less than in case of stroke alone.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, platelet inhibitors such as aspirin have not been found to affect MPV. 16,17 Hypoglycemic or hypolipidemic decreases the MPV as well as plasma glucose level 18 or cholesterol levels. 19 Hundreds of participants of this study are taking hypoglycemic agent or hypolipidemic agent, may decrease the association between MPV and hypertension incidence, because individuals with diabetes or dyslipidemia have higher hypertension incidence even on treat.…”
Section: Discussionmentioning
confidence: 99%
“…In a study where Karagöz et al and Pedersen et al searched platelet number in cases with lung cancer, they stated that platelet number in malignant cases was higher than those in healthy individuals [8][9][10][11][12][13][14][15][16][17][18][19] . In a research where Jun et al searched platelet parameters in middle age cancerous cases, MPV, platelet distribution is still diffi cult to diagnose intestine obstruction under emergency conditions in spite of up-to-date diagnostic and therapeutic modalities.…”
Section: Discussionmentioning
confidence: 99%